BUREAUCRATIC REFORM IN POPULATION ADMINISTRATION SERVICES IN TILONGKABILA DISTRICT BONE BOLANGO REGENCY - A Sahi, Nirmala; Rivani Luawo, Salma; Nuna, Muten; Bilondatu, Nikma (LP2M Universitas Bina Mandiri Gorontalo, 2023)
Changes in various things become society's criteria in assessing public service performance. There are many reasons why there are many changes in existing public services, including the demands of an increasingly modern society, the increasing development of technology and globalization, competition with the private sector, changes in people's mindsets and many other things that cause the need to improve the quality of public services. Population administration services are one of the areas that is the task of the Tilongkabila District Government, Bone Bolango Regency, to organize. Meanwhile, the bureaucratic reform that is about to be implemented is intended to run optimally, so that it can help the government in realizing excellent service. This research was conducted to determine bureaucratic reform in population administration services in Tilongkabila District, Bone Bolango Regency. This research uses a qualitative descriptive approach method. The results of this research show that bureaucratic reform in population administration services in Tilongkabila District, Bone Bolango Regency is based on Komarudin's theory, namely Institutions, Human Resources for Apparatus, Administration or Management, Supervision, Accountability of Apparatus, Quality Services and Changes in mindset and work culture. (culture-set) works quite well. Therefore, theoretically, it is hoped that this research will ensure that the Tilongkabila District Government, Bone Bolango Regency, will continue to improve and improve bureaucratic performance, so that good governance will be created, especially in providing excellent population administration services.